Sistem Respon Satu Derajat Kebebasan terhadap Beban Harmonik pada Struktur Portal 2D - Muis Alie, Muhammad Zubair; Suci, Indah Melati; Rajmi, Astika; Arafat, Andi Muhammad Alfian (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2019)
Response of One Degree of Freedom System to Harmonic Loading on the structure idealized as single degree of freedom systems excited harmonically, that is structure subjected to force or displacement where the magnitude may be represented by a sine or cosine function of time. This type of excitation results one of the most important motions in the study of mechanical vibrations as well as in applications to structural dynamics. Structure is very often subjected to the dynamic action such cyclic load acting and resulting response due to the the unavoidable load eccentricity. The objective of the present study is to analyze the response of one-degree of freedom system to the portal 2D. The structure is modelled and analyzed using finite element method. The result obtained by FE method is joint displacement of the structure.